2022
DOI: 10.3390/children9091283
|View full text |Cite
|
Sign up to set email alerts
|

Can Physical Exercise Promote the Development of Teenagers’ Non-Cognitive Ability?—Evidence from China Education Panel Survey (2014–2015)

Abstract: Background: With the development of educational philosophy, physical exercise is considered to be an important factor in the development of individual cognitive abilities in adolescents. However, the effects of physical exercise on non-cognitive abilities in adolescents remain inadequate. Objective: This study examined the effect of physical exercise on non-cognitive ability and further examined the differences in this effect in different groups. Methods: Survey data on non-cognitive ability, physical exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…③The development of non-cognitive skills in physical activity showed some group differences, with girls performing better than boys in non-cognitive skills [11] , and for both male and female adolescents, increasing physical activity by 1 time per week would be 8 percentage points more effective in reducing the probability of absenteeism for males than for females, about 8% more effective in trusting strangers for females than for males, and 6.7 percentage points more effective in improving people skills for females than for males. The effect of increasing the frequency of physical activity was 6.7 percentage points higher for females than for males, and the effect of reducing the number of bad mood days per week was 2.9 percentage points higher for males than for females.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…③The development of non-cognitive skills in physical activity showed some group differences, with girls performing better than boys in non-cognitive skills [11] , and for both male and female adolescents, increasing physical activity by 1 time per week would be 8 percentage points more effective in reducing the probability of absenteeism for males than for females, about 8% more effective in trusting strangers for females than for males, and 6.7 percentage points more effective in improving people skills for females than for males. The effect of increasing the frequency of physical activity was 6.7 percentage points higher for females than for males, and the effect of reducing the number of bad mood days per week was 2.9 percentage points higher for males than for females.…”
Section: Discussionmentioning
confidence: 98%
“…The previous studies related to the effects of physical activity on adolescents' cognitive abilities and academic performance can be traced back to the 1950s, and after the 20th century, a number of remarkable research results emerged under the influence of theories and research methods related to cognitive neuroscience [5] . For the relationship between physical calcination and noncognitive abilities, there are two main aspects, one is the influence of non-cognitive abilities on children's participation in physical calcination, such as sports and personality [6] , the influence of personality traits on physical activity participation [7] , and the relationship between physical activity and mental health [8] ; the second is the influence of physical activity on The study of the effects and mechanisms of adolescents' non-cognitive abilities is a recent scholarly attention [9], [10], [11] . Non-cognitive abilities were first proposed by economists Bowles and Gintis in 1976, who argued that individuals' abilities can be divided into cognitive and non-cognitive abilities, where noncognitive abilities have an important impact on individuals' academic achievement and earnings in the labor market [12] , and non-cognitive skills include personality traits, such as emotional stability, reliability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Appropriate physical activity can help adolescents establish and strengthen communication with peers, reduce negative emotions, and improve school adjustment [10]. Some studies have also found that adolescents' participation in physical activity leads to better integration into the group, an essential safeguard for adolescents to adapt to school life [11]. Based on this, this study proposes Hypothesis H1: Physical activity among high school students can positively predict school adjustment.…”
Section: Introductionmentioning
confidence: 87%